Conservation of Great Bustard (Otis Tarda) Population of the Mosoni-Plain - A Success Story - Faragó Sandor (Sciendo, 2014)
At the turn of the 19-20th centuries, the Great Bustard population of the Kisalföld (Little Hungarian Plain) numbered 4000 specimens. By 1990, only about 100 individuals remained in the Hungarian and Austrian territories. Of the many possible negative factors of current times, the greatest pressure on the Great Bustard population stems from unfavorable crop structures, extensive use of intensive agricultural technologies and predation. During the past decades, we have seen a shift in nesting place locations from natural-like habitats to agrar-type habitats. This change may be explained by the more favorable structure and microclimate of this latter habitat type paralleled with greater food source availability. In order to escape this ecological trap, we have to engage in active conflict resolution that provides protection the region's Bustard population.